Nephelometry determined serum immunoglobulin isotypes in healthy Thai children aged 2-15 years - Raweerat Sitcharungsi (2018)
Knowledge of what constitute normal serum immunoglobulin (Ig) concentrations are important for the diagnosis of immunologic disorders. Data on normal Ig evaluated by nephelometry are limited in healthy Asian children, none being available for Thai children. One hundred and forty-eight healthy Thai children aged 2-15 years were tested for serum immunoglobulins G, A, M, G1, G2, G3, and G4 (Ig G, A, M, G1, G2, G3, and G4) by nephelometry. Sixty-three percent were girls of median interquartile range age 6.9 (4.8-9.7) years. The geometric means for each Ig were summarized and categorized by age. Statistical analyses were used to compare Igs between sexes and age groups, and to compare IgG in this study with data from other published studies. The average ratios of IgG subclasses/IgG for Ig G1:2:3:4 were 66:22:5:7%. IgG, IgA, IgG2, and IgG3 concentrations showed a gradual increase with increasing age. There were no significant sex differences for any immunoglobulin isotype (P= 0.971). Our mean IgG concentration was lower than that measured by the radial diffusion method in healthy Thai children (P < 0.05). In all age groups, the mean IgG concentration in our study was significantly higher than that reported in Turkish and USA children, evaluated by the nephelometric and radial diffusion techniques, respectively (both P < 0.001). This study provides information about normal Ig concentrations measured by nephelometry in healthy Asian children and illustrates the importance of ascertaining normal Ig values for age- and ethnic-matched controls using the same assay to diagnose immunologic disorders correctly. © 2012 The Societies and Blackwell Publishing Asia Pty Ltd.